Genetic characterization of Italian patients with Bardet-Biedl syndrome and correlation to ocular, renal and audio-vestibular phenotype: identification of eleven novel pathogenic sequence variants. Issue 1 (December 2017) - Esposito, Gabriella; Testa, Francesco; Zacchia, Miriam; Crispo, Anna; Di Iorio, Valentina; Capolongo, Giovanna; Rinaldi, Luca; D'Antonio, Marcella; Fioretti, Tiziana; Iadicicco, Pasquale; Rossi, Settimio; Franzè, Annamaria; et al.
Abstract Background Bardet-Biedl syndrome (BBS) is a rare genetic disorder that features retinal degeneration, obesity, polydactyly, learning disabilities and renal abnormalities. The diagnosis is often missed at birth, the median age at diagnosis being 9 years. In the attempt to shed light on BBS and improve its diagnosis and treatment, we evaluated the genotype-phenotype relationship in patients with a molecular diagnosis of BBS. Methods We analyzed three common BBS genes, BBS1, BBS10 andBBS2, in 25 Italian patients fulfilling the clinical criteria of BBS. In 12 patients, we identified gene-specific biallelic variants and thus correlated genotype to the ophthalmic, renal and audio-vestibular phenotypes. Results At least one sequence variant was found in 60% of patients. The most common mutated gene wasBBS1 followed byBBS10 . Of the 17 sequence variants we found, 11 have not previously been associated with BBS. In 12 patients, we identified biallelic pathogenic variants; they had retinitis pigmentosa with early onset of visual impairment. However, retinal dystrophy was less severe in patients withBBS1 than in those withBBS10 variants. Overall, we found a high prevalence of renal dysmorphism and dysfunction. Notably, patients withBBS10 variants had the most severe renal impairment, which resulted in a critical decline in renal function. All the patients who underwent audio-vestibular evaluation had dysfunction of the cochlear outer hair cells, thus confirming the presence of hearing defects. Conclusion BBS1, BBS2 andBBS10 are major causative genes in Italian BBS patients.BBS10 was associated with the worse outcome in terms of the renal, ocular and audiovestibular phenotypes. Cochlear dysfunction should be included among the hallmarks of BBS.